PENGARUH LINGKUNGAN KERJA, MOTIVASI KERJA, DAN PENGEMBANGAN KARIR TERHADAP PERFORMANSI KARYAWAN PT. ANGKASA PURA AVIASI - Ardiansyah Toy, Jefry; Lumbanraja, Prihatin; Purnomo Wibowo, Rulianda (Penerbit Lafadz Jaya, 2025)
This study aims to analyze the influence of the work environment, work motivation, and career development on employee performance at PT. Angkasa Pura Aviasi. These variables were selected because they are considered key factors that can affect both individual and organizational productivity and success overall. The research employs a quantitative approach with data collection through a survey distributed to 100 employees from various departments and job levels within the company. The collected data are then analyzed using multiple regression analysis to examine the effect of each independent variable on the dependent variable, namely employee performance. The results indicate that the work environment, work motivation, and career development simultaneously have a significant impact on employee performance, as shown by a p-value < 0.05; the variables also demonstrate positive and significant partial effects. Specifically, work motivation has the greatest influence on employee performance, followed by career development and the work environment. These findings reinforce the theory that motivational factors and adequate opportunities for career development are crucial in enhancing employee productivity and loyalty. Furthermore, a conducive and supportive work environment plays an essential role in creating a healthy and motivating workplace atmosphere. The implications of this research provide practical insights for the management of PT. Angkasa Pura Aviasi, suggesting that they should increase their focus and investment in these factors through innovative and sustainable policies and programs. With these strategies, the company is expected to improve employee performance more effectively, ultimately supporting the achievement of the company's vision and mission, enhancing competitiveness, and ensuring long-term sustainability.